Jens Munk (1579-1628) - Schledermann, Peter (ARCTIC, 1985)
. In 1618 the Danish King Christian IV ordered Munk to ready a major expedition to embark for East India via Cape Horn. Tirelessly, Munk organized the ships, the men, the provisions, and the thousand details involved in such an undertaking. To his astonishment, however, the command was not to be his; it fell to a man of suitable nobility, Ove Giedde. . The future was bleak, but Munk was not easily discouraged. He approached the king with a plan to launch another expedition to the far east, this one to proceed through the assumed northwest passage. . Munk chose 61 men and two vessels, one the heavy mothership the Unicorn (Enhjoringen) and the other the light reconnaissance vessel the Lamprey (Lampren). . They crossed the Atlantic and entered Frobisher Bay by mistake, and when they finally found their way into Hudson Strait, they accidentally sailed deep into Ungava Bay before they got back on the true course. By the time they reached Hudson Bay on September 4th, signs of scurvy were already present in the men. A savage storm forced Munk to make a spectacular entry with the Unicorn into a protected bay on the west coast at the site of present-day Churchill. The Lamprey soon followed, and the place was named Nova Dania. A wintering was clearly in store for the expedition, and little time was wasted in getting the ships to safe location. . Aware of the dangers of scurvy, Munk encouraged his men to eat berries and roots as long as possible, and the ravages of the dread disease were postponed for a while. Nevertheless, on the 21st of November one man died of scurvy, and another followed soon after. . On July 16 Munk began another, perhaps the greatest, epic journey. One can only imagine the next 67 days in ice-infested and storm-swept seas, across Hudson Bay, through the Strait, round the southern tip of Greenland, and forever eastward. The master mariner got the ship through it all, and on the 20th of September he spotted the distant mountains on the west coast of Norway. No hero's welcome awaited Jens Munk. One of ...